Examining Cytokines Levels in Individuals with Metabolic Syndrome and Non-metabolic Syndrome - Lingidi Jhansi Lakshmi; Doddigarla Zephy; Abdul Rab Alli (Medical Science: Trends and Innovations Vol. 1, 2025)
Background: Metabolic syndrome is characterized by abnormalities in blood pressure, blood sugar, waist circumference, and cholesterol or triglyceride levels. Cytokines, produced by immune system cells, act as messengers to regulate inflammation and immune response. Studies have demonstrated the contribution of cytokines to metabolic syndrome. Inflammatory cytokines such as Interleukin-6 (IL-6) and Tumor necrosis factor alpha (TNF-\(α\)) have been associated with metabolic syndrome and insulin resistance, a hallmark of the condition. Aim: The unique aspect of this study is its primary focus on determining whether there is a distinction in inflammatory markers between individuals with metabolic syndrome and those without the condition. Material and Methods: The study included 50 patients with metabolic syndrome and 50 healthy controls. The research was conducted at Indore Index Medical College & Research Centre. After obtaining approval, the study’s researchers commenced their work. Each subject provided informed consent prior to the study. Individuals with type 1 diabetes or clinical symptoms for fewer than five years and documented T2DM duration were excluded. Healthy controls (non-metabolic syndrome) were individuals without diabetes, multivitamin use, or comorbidities. Statistical Analysis: Regressions were used to determine the relationship between two variables. Additionally, percentages were calculated. A significance level of p < 0.05 was considered significant. Conclusion: The significance of these results cannot be overstated. The study’s findings unequivocally demonstrate that both pro-inflammatory and anti-inflammatory cytokines contribute to the development of secondary illnesses associated with metabolic syndrome. The study concluded that both pro-inflammatory and anti-inflammatory cytokines play a role in the development of secondary conditions associated with metabolic syndrome. Moreover, these analyzed cytokines may serve as biomarkers for early detection and diagnosis of secondary complications in individuals with metabolic syndrome.